Implementation of Religious Culture in Fostering Student Discipline Attitudes in Elementary Schools - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2023)
The aims of this study were (1) To find out the implementation of religious culture in cultivating the discipline attitude of students at SD Negeri 4 Bilokka (2) To find out the supporting and inhibiting factors in implementing religious culture as an effort to foster disciplined attitudes of students at SD Negeri 4 Bilokka The approach used in this study is a qualitative approach. Research data obtained by interview and documentation methods. Based on the results of the study, it can be concluded that the implementation of religious culture applied in SD Negeri 4 Bilokka can foster a disciplined attitude in students. Religious culture which is the inculcation of religious values through habituation is carried out by implementing routine activities that go well, while religious cultural activities in SD Negeri 4 Bilokka include: promoting a culture of smiles, greetings and greetings, Duha prayer and congregational prayers Ah, congregational midday prayers, Qur'an Education, Caring Friday, women's studies, lively music, and Islamic boarding schools for Ramadhan. With the activities carried out regularly or continuously, it will become a habit and can foster student discipline. As for the efforts made to continue to carry out this discipline, namely by having regulations in the form of points, sanctions or punishments set, and also awards given, so that student discipline can continue to be carried out properly.